Hinduism and Adult Learning: Fostering a Mind-Body Connection - Swathi Nath Thaker (Adult Education Research Conference, 2010)
The Western notions of learning have, and still, dominate the field of adult education, with non-cognitive forms of learning such as somatic learning and spirituality only recently emerging. While much of the Western literature on learning and knowing suggest that the mind and body are split, a number of cultures around the world do not believe in this dichotomy, and Hinduism is no exception. Hinduism, which is said to be over four thousand years old, defines itself according to the Vedas, the most ancient body of religious literature. While much of this content has long been unknown to most Hindus, it is still regarded as an absolute authority which reveals the fundamental truth. It is through these texts, which were originally shared vocally, that individuals come to appreciate multiple ways of learning and connecting to the world. Though Western belief teaches that an individual is empowered through himself or herself, Hinduism argues that true empowerment emerges through an understanding of the sources of knowledge, not just its components, which in turn leads to unity with the universe. Thus, life for Hindus becomes not merely about learning facts and figures, but also about developing wisdom by forming a connection between the mind, body, and spirit.